Diskursus Riba Penjualan Langsung Berjenjang Syariah (PLBS) Paytren Di Kalangan Ulama Penceramah Dan Ulama Entreprenuer - Nurainun Mangunsong (UIN Sunan Kalijaga Yogyakarta, 2020)
Sharia Tiered Direct Selling (PLBS) or popularly called multilevel marketing (MLM) in the sharia perspective is still being debated. The element of usury and gharar that can be seen from this practice of multilevel marketing or multilevel pyramid has made many scholars indoctrinate it as haram. However, along with the development of e-commerce or digital online facilities that can be accessible, faster, cheaper, and unlimited, PLBS continues to be developed into an attractive business and sharia as an effort to answer business competitions and to channel for the needs of muslims. This research tries to look at the business practice of PayTren PLBS in the copetititions and sharia context, and the response of Preaching Scholars and Entrepreneur Scholars in the online media related to PayTren PLBS.